Choice of foreign R&D entry mode and its relation to firm performance: A firm-level analysis for Switzerland and Austria - Heinz Hollenstein; Martin Berger (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
The objective of this study is to identify the determinants of a firm's foreign entry mode choice and the relationship between mode selection and firm performance for the specific case of R&D-a topic not yet investigated in entry mode research. Separate estimates of a Heckman selection model for Austria and Switzerland based on comparable firm-level data and variable specification show for both countries that the OLI model is well-suited to explain not only the propensity to invest in R&D abroad but also the related choice between an equity-based and a non-equity governance mode. Moreover, the research reveals that foreign R&D activity is positively related to firm performance and that this relationship is stronger in the case of an equity-based mode of governance, however only in the Swiss case. The differences between the two countries primarily reflect the much higher degree of internationalisation of the Swiss economy.
Keywords: F23; F61; L24; O32; 330; Internationalisation of R&D; Foreign R&D entry mode choice; International R&D co-operation; Foreign R&D governance and firm performance